Should all enmeshed families be regarded as dysfunctional: |a study of the circumplex model of marital and family systems - Levi, Hanna R. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
The purpose of the present study was to show that Turkish families are quite cohesive and that this cohesion does not necessarily lead to pathology in the family. The main concept under investigation was the level of family cohesiveness, that is the level of emotional bonding among family 'members. Specifically, the cross cultural validity of the findings generated from the Circumplex Model of Marital and Family Systems were of concern. Three groups; "non-clinic" 'low educational level, "nonclinic" high educational level and "clinic" low educational level, each consisting of twenty married couples served as subjects. Level of family cohesion and marital satisfaction was assessed by The Third Family Adaptability and Cohesion Evaluation Scale (FACES III). It was hypothesized that "non-clinic" Turkish families would function at the higher end of the cohesion continuum and that they would be satisfied with their current family functioning while "clinic" Turkish families would function at the two extreme ends of the cohesion continuum and that they would be less satisfied compared to "non-clinic" families'. The two "non-clinic" samples showed levels of functioning high on the cohesion continuum, and they were satisfied. However, the "clinic" sample too was found to be functioning at similar high levels on the cohesion continuum but their level of satisfaction was significantly lower than the IInon-clinic" families' level of satisfaction. These findings supported the contention that high family cohesion is a cultural norm in Turkish families. Thus, while the so called 'cohesion dimensionJseems to assess levels of family functioning in terms of cohesion, its relation to pathology seems to be questionnable.
Keywords: Circumplex Model of Marital and Family Systems.